Planar RF and microwave bandpass filters via slot-line and stub-line inverters - Zhou, Yiying. (2013)
Band-pass filter is significant building block in modern communication system. Nowadays, high performance band-pass filters are needed in many microwave systems. Thus this project presents a narrow band-pass filter with hybrid slot-line and stub-line inverters.